Demokratie und zivile Kontrolle über das Militär in Thailand und Indonesien - Lorenz, Philip; Chambers, Paul (Asien, 2010)
It is widely accepted that civilian control of the military is defining element of democratic consolidation. This article demonstrates how lack of civilian control negatively affects democracy in Indonesia and Thailand. Based on newly developed concept of civilian control and the concept of embedded democracy it analyzes the direct effects of weak civilian control on civilian governments' effective power to govern and its indirect effects on the other partial regimes of democracy. Our results show that civilian control is weak in both countries. However, while Indonesia's electoral regime, the core of democracy, is only marginally affected by military interference, the fairness of Thai elections suffers from massive intrusions of the armed forces. Still, lacking civilian control in Indonesia indirectly aggravates defects in other partial regimes of democracy, such as the violation of civil rights or corruption. Indonesia's electoral regime is only affected on the subnational level.